Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To simplify the expression [tex]\(\sqrt{80} - 2 \sqrt{45}\)[/tex], follow these steps:
1. Simplify [tex]\(\sqrt{80}\)[/tex]:
- [tex]\(\sqrt{80}\)[/tex] can be broken down into [tex]\(\sqrt{16 \cdot 5}\)[/tex].
- Use the property [tex]\(\sqrt{ab} = \sqrt{a} \cdot \sqrt{b}\)[/tex]:
[tex]\[ \sqrt{80} = \sqrt{16 \cdot 5} = \sqrt{16} \cdot \sqrt{5} \][/tex]
- Since [tex]\(\sqrt{16} = 4\)[/tex]:
[tex]\[ \sqrt{80} = 4 \cdot \sqrt{5} \][/tex]
Numerically, [tex]\(\sqrt{80} \approx 8.94427190999916\)[/tex].
2. Simplify [tex]\(2 \sqrt{45}\)[/tex]:
- [tex]\(\sqrt{45}\)[/tex] can be broken down into [tex]\(\sqrt{9 \cdot 5}\)[/tex].
- Use the property [tex]\(\sqrt{ab} = \sqrt{a} \cdot \sqrt{b}\)[/tex]:
[tex]\[ \sqrt{45} = \sqrt{9 \cdot 5} = \sqrt{9} \cdot \sqrt{5} \][/tex]
- Since [tex]\(\sqrt{9} = 3\)[/tex]:
[tex]\[ \sqrt{45} = 3 \cdot \sqrt{5} \][/tex]
- Multiply by 2:
[tex]\[ 2 \sqrt{45} = 2 \cdot (3 \cdot \sqrt{5}) = 6 \cdot \sqrt{5} \][/tex]
Numerically, [tex]\(2 \sqrt{45} \approx 13.416407864998739\)[/tex].
3. Combine the simplified parts:
- The expression becomes:
[tex]\[ \sqrt{80} - 2 \sqrt{45} = 4 \cdot \sqrt{5} - 6 \cdot \sqrt{5} \][/tex]
- Since [tex]\(4 \cdot \sqrt{5}\)[/tex] minus [tex]\(6 \cdot \sqrt{5}\)[/tex] is [tex]\((4 - 6) \cdot \sqrt{5}\)[/tex]:
[tex]\[ \sqrt{80} - 2 \sqrt{45} = -2 \cdot \sqrt{5} \][/tex]
Numerically, this results in [tex]\(\approx -4.47213595499958\)[/tex].
So, the simplified expression is [tex]\(-2 \cdot \sqrt{5}\)[/tex].
The results you should enter are:
1. [tex]\(\sqrt{80} \approx 8.94427190999916\)[/tex]
2. [tex]\(2 \sqrt{45} \approx 13.416407864998739\)[/tex]
3. The final simplified result: [tex]\(-2 \cdot \sqrt{5} \approx -4.47213595499958\)[/tex]
1. Simplify [tex]\(\sqrt{80}\)[/tex]:
- [tex]\(\sqrt{80}\)[/tex] can be broken down into [tex]\(\sqrt{16 \cdot 5}\)[/tex].
- Use the property [tex]\(\sqrt{ab} = \sqrt{a} \cdot \sqrt{b}\)[/tex]:
[tex]\[ \sqrt{80} = \sqrt{16 \cdot 5} = \sqrt{16} \cdot \sqrt{5} \][/tex]
- Since [tex]\(\sqrt{16} = 4\)[/tex]:
[tex]\[ \sqrt{80} = 4 \cdot \sqrt{5} \][/tex]
Numerically, [tex]\(\sqrt{80} \approx 8.94427190999916\)[/tex].
2. Simplify [tex]\(2 \sqrt{45}\)[/tex]:
- [tex]\(\sqrt{45}\)[/tex] can be broken down into [tex]\(\sqrt{9 \cdot 5}\)[/tex].
- Use the property [tex]\(\sqrt{ab} = \sqrt{a} \cdot \sqrt{b}\)[/tex]:
[tex]\[ \sqrt{45} = \sqrt{9 \cdot 5} = \sqrt{9} \cdot \sqrt{5} \][/tex]
- Since [tex]\(\sqrt{9} = 3\)[/tex]:
[tex]\[ \sqrt{45} = 3 \cdot \sqrt{5} \][/tex]
- Multiply by 2:
[tex]\[ 2 \sqrt{45} = 2 \cdot (3 \cdot \sqrt{5}) = 6 \cdot \sqrt{5} \][/tex]
Numerically, [tex]\(2 \sqrt{45} \approx 13.416407864998739\)[/tex].
3. Combine the simplified parts:
- The expression becomes:
[tex]\[ \sqrt{80} - 2 \sqrt{45} = 4 \cdot \sqrt{5} - 6 \cdot \sqrt{5} \][/tex]
- Since [tex]\(4 \cdot \sqrt{5}\)[/tex] minus [tex]\(6 \cdot \sqrt{5}\)[/tex] is [tex]\((4 - 6) \cdot \sqrt{5}\)[/tex]:
[tex]\[ \sqrt{80} - 2 \sqrt{45} = -2 \cdot \sqrt{5} \][/tex]
Numerically, this results in [tex]\(\approx -4.47213595499958\)[/tex].
So, the simplified expression is [tex]\(-2 \cdot \sqrt{5}\)[/tex].
The results you should enter are:
1. [tex]\(\sqrt{80} \approx 8.94427190999916\)[/tex]
2. [tex]\(2 \sqrt{45} \approx 13.416407864998739\)[/tex]
3. The final simplified result: [tex]\(-2 \cdot \sqrt{5} \approx -4.47213595499958\)[/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.